Development of E-Comic Teaching Materials with a local Wisdom Theme to Enhance High School Student’s Historical Awareness - Nontje Deisye Wewengkang; Rahmat Rahmat; Rohim Rohim; Saefuddin Saefuddin; Iwan Ramadhan; Al-Amin Al-Amin (STAI Hubbulwathan Duri, 2024)
Historical awareness is critical for students because it fosters a deeper understanding of the past, strengthens their ability to see connections between historical events, and supports the development of national identity. Effective teaching materials are needed to increase this awareness. This research aims to develop and evaluate e-comic teaching materials designed to increase students' historical awareness. Research and Development (RD) includes four stages: defining (data collection), designing (creating teaching materials), developing (expert testing), and disseminating (application of validated teaching materials). The research subjects consisted of 6 validity experts, 2 teachers, 30 and 90 grade XII students to assess the pragmatism and effectiveness of the teaching materials developed. Data collection was carried out through validity and practicality questionnaires, observations, interviews, and student assessment sheets. The validity and practicality of teaching materials are analyzed qualitatively, while their effectiveness is measured quantitatively with the T and N-Gain tests. The research results show that e-comic teaching materials have a validity score of 4.02, which indicates strong validity in increasing students' historical awareness. A practicality score of 4.07 indicates ease of use, making it easier for students to access the material. The T-test with a significance of 0.001 shows a significant effect of e-comics, while the N-Gain test shows an increase in students' historical awareness by 66%, indicating the effectiveness of this intervention in achieving learning objectives. The use of e-comics teaching materials in the classroom has proven to be feasible, practical, and useful for increasing students' historical awareness, thus contributing significantly to history education.